Evolving Loyalties: A Provincial Printer in Revolutionary Bordeaux - McLeod, Jane (Mémoires du livre / Studies in Book Culture, 2010)
The author examines the career of Simon Lacourt, a Bordeaux printer who was guillotined during the French Revolution, and explores the ways in which printers’ milieu and patrons determined their printing choices. Lacourt -- the last in a long line of King’s printers in Bordeaux -- was one of the most privileged and connected printers in the reign of Louis XVI when he made the move into revolutionary printing and became a newspaper printer and the official printer for the Department of the Gironde. His printing business prospered until the summer of 1793 when he became the official printer of the commission populaire, the body that led the federalist revolt in Bordeaux, a fateful decision dictated by his social, familial and political milieu and one that left him vulnerable after the revolt failed. During his trial he was accused of trying to destroy his country and his fate raises questions about printer responsibility during the Revolution.